Precarity prevented or reinforced? Migrants' right to change employers in the recast of the EU Single Permit Directive - De Lange, Tesseltje; Falkenhain, Mariella (Frontiers in Sociology, 2024)
Labor migration policies within the European Union and its Member States typically address two conflictive labor market policy goals. They aim to attract and retain foreign workers in a situation of labor shortage, while at the same time protecting the national workforce from additional labor market competition.The balancing of these two goals is commonly resolved in favor of nationals and with fewer rights for migrant workers. It is precisely this nexus between migrant rights and the protection of the national workforce that is central to the understudied question of whether and under what conditions migrant workers from third countries (i.e. non-EU countries) may change their employer to quit low-quality work or exploitative employment, or for career reasons. Building on scholarly discussions on employer dependency and bureaucratic complexity as general sources of migrant precarity, as well as on international and EU law on the rights of migrant workers, this article presents three policy variations of the right to change employers currently in place in the European context. Thereby we fill a gap in the literature on labor migration, labor market regulation, and migrant workers' rights. To illustrate the mixed ambitions of EU institutions to reduce migrant precarity the article then presents and critically discusses the ongoing high-level negotiations over the recast of the EU Single Permit Directive 2011/98 that are centered around the right to change employers.